Clinical Observation on Auricular Acupressure for Primary Dysmenorrhea: A Study Protocol for a Randomized Clinical Trial - Liu L; Hu J; Lu J; Yang J (Journal of Pain Research, 2023)
Lumin Liu,1,* Junwei Hu,1,* Junjie Lu,2 Jiaxin Yang3 1Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Social and Behavioral Sciences, Harvard University T.H. Chan School of Public Health, Boston, MA, USA; 3Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiaxin Yang, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, 110 Ganhe Road, Hongkou District, Shanghai, 200437, People’s Republic of China, Email love_yangjiaxin@163.comPurpose: The objective of this study is to evaluate the immediate and time-dependent effects of AA in treating PD and assess its safety.Methods/Design: This study is a randomized, single-blinded, controlled trial that will enroll 92 patients in a 1:1 allocation ratio. Patients will be assigned to either the treatment group (n=46) or the control group (n=46). During the first menstrual period, the treatment group will receive AA treatment, while the control group will receive sham AA treatment for 7 days. The second menstrual period will serve as the follow-up period. The primary outcome measure is the Visual Analog Scale (VAS) score 30 min after the first treatment. Secondary outcome measures include the VAS score immediately after the first treatment, onset time of analgesic effect, duration of pain, extra dosing rate of ibuprofen, and change of the Menstrual Distress Questionnaire (MDQ) score. The outcomes will be assessed at baseline, during the intervention period, and during the follow-up period.Conclusion: The study results will provide evidence on the efficacy and safety of AA in managing PD by analyzing its immediate effect, time-effect relationship, and reduction of painkiller use.Trial Registration: Chinese Clinical Trial Registry (ChiCTR2300069741).Keywords: acupressure, dysmenorrhea, menstrual pain, ear